Strong Teens for Healthy Schools: Protocol for evaluating a youth nutrition, physical activity, and civic engagement protocol - MacMillan Uribe, Alexandra L.; George, Alisha; McNeely, Andrew; Xin, Lucy; Largacha Cevallos, Erika; Rethorst, Chad; Seguin Fowler, Rebecca A.; Szeszulski, Jacob (Frontiers in Public Health, 2025)
Early prevention and treatment of metabolic syndrome (MetS) through healthy eating and physical activity are essential for reducing chronic disease risk among youth. The school food and physical activity environment significantly influences children's health behaviors. Yet, interventions targeting schools' health environments are sparse, and none empower middle school students to be change agents. We describe the process and rationale for evaluating Strong Teens for Healthy Schools (STHS), a multilevel middle school civic engagement program promoting healthier school environments through student-driven projects. We will test the efficacy of STHS for reducing MetS risk and improving positive youth development outcomes among students at middle schools where >40% of students identify as Black/African American or Hispanic/Latino (n = 20 schools; n = 20–25 students per school) through a pilot cluster randomized controlled trial. Schools randomized to STHS intervention will participate in 16 modules on civic engagement, healthy eating, and physical activity, and schools randomized to the delayed intervention group will receive the curriculum one year later. Student outcomes will be measured at four points: within 1 month of recruitment, at end of intervention, at start of next school year, and at end of next school year. Secondary outcomes include students' perceptions of peers' health behaviors and environmental assessments through photovoice. Evaluating the efficacy of STHS in improving MetS and promoting positive youth development will provide initial evidence on improving physical activity and nutrition outcomes at individual, social, and environmental levels, paving the way for larger-scale studies and informing dissemination efforts.Clinical Trial Registry Number:ClinicalTrials.gov ID NCT05867433.